1981
DOI: 10.2466/pms.1981.52.1.75
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Children's Perceptions of Dominance Relations

Abstract: The factors which contribute to children's perceptions of dominance are unclear although evidence for dominance hierarchies has been obtained through children's rankings of toughness in their classes. Three potentially influential factors were examined in the present study: who is being ranked (self or other), where the child fits in the class hierarchy (high or low rank), and what terms are used for ranking (“gets own way” or “is toughest”). Fifty-two fourth grade students ranked themselves and their classmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
2
7
1
Order By: Relevance
“…That is, the assessment of dominance among the three groups of individuals was divergent. These results contradict the findings of Pickert and Wall (1981), indicating the need for further research on perceptions of dominance. Sluckin (1980) investigated the existence of dominance hierarchies among preschool children.…”
Section: Children and Dominancecontrasting
confidence: 82%
See 1 more Smart Citation
“…That is, the assessment of dominance among the three groups of individuals was divergent. These results contradict the findings of Pickert and Wall (1981), indicating the need for further research on perceptions of dominance. Sluckin (1980) investigated the existence of dominance hierarchies among preschool children.…”
Section: Children and Dominancecontrasting
confidence: 82%
“…In an analysis of children's perceptions of dominance, Pickert and Wall (1981) conceptually defined dominance as "manipulation and control of other's behavior" (p. 175-6). Dominance was then operationally defined as "toughness" and "Getting one's own way."…”
Section: Children and Dominancementioning
confidence: 99%
“…In examining these links, we consider perceptions of power and dominance within the peer group as well as indices of perceived popularity and sociometric status. Traditionally, dominance is a term applied to individuals who are able to actively manipulate and influence others' behavior [e.g., Maccoby and Jacklin, 1974;Pickert and Wall, 1981]. Accordingly, we hypothesized that peer perceptions of social power would be more strongly related to perceived popularity than likeability.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these investigators found that individual children tended to place themselves higher in the hierarchy tiian did their peers. Pickert and Wall (1981) also found this to be the case for "toughness" for both high-and low-status individuals, although it was only the case for low-status children on "getting own way"; when this latter term was used, high-status children underranked themselves. Besides status, another factor that has been found to add variability to the perceived hierarchies is the sex of the raters and nitees.…”
mentioning
confidence: 91%